Waste Reduction on Personality Action System of Daily/Piece-rated Process - Benedictus Rahardjo (International Journal of Industrial Research and Applied Engineering, 2018)
PT. X is a multinational company that works in the consumer goods sector. PT. X has many departments and one of them is the Human Resources (HR) Department whose role is to maintain all of the employees under PT. X. The HR Department also has some subfunctions. One of them is HR Services. Employees that work with PT. X are divided into two categories: monthly employees and daily/piece-rated employees. One of the processes that HR Services provides for the daily/piece-rated employees is ePAF daily/piece-rated, which can be monitored by a verification process. If an ePAF is not verified, then it is possible for the ePAF process to be denied and that is a waste that can cause over-processing for HR Services. There were 750 ePAF denials in 2016 with an average processing time of 1.78 hours needed to resubmit each process. An analysis was done using a Pareto Chart and Fishbone Diagram to reduce the time wasted and to look for countermeasures for each of the root causes. The Pareto Chart shows three major problems occurring. These are: errors in the closing date, errors in the transaction date, and errors in the supporting document. The root causes of the problem come from human error, method errors, and system classification errors. The solutions proposed are expected to reduce the numbers of ePAF denials by around 51.2%.